2011
DOI: 10.1063/1.3551696
|View full text |Cite
|
Sign up to set email alerts
|

Penetration and screening of perpendicularly launched electromagnetic waves through bounded supercritical plasma confined in multicusp magnetic field

Abstract: The question of electromagnetic wave penetration and screening by a bounded supercritical ͑ p Ͼ with p and being the electron-plasma and wave frequencies, respectively͒ plasma confined in a minimum B multicusp field, for waves launched in the k Ќ B o mode, is addressed through experiments and numerical simulations. The scale length of radial plasma nonuniformity ͉͑n e / ͑‫ץ‬n e / ‫ץ‬r͉͒͒ and magnetostatic field ͑B o ͒ inhomogeneity ͉͑B o / ͑‫ץ‬B o / ‫ץ‬r͉͒͒ are much smaller than the free space ͑ o ͒ and guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…29,30 The vacuum TE 11 mode is modified due to the plasma dispersion, hence the axial wave magnetic field amplitude can be expressed in terms of vacuum electric field amplitude E o for a cylindrical waveguide of radius a as 32 B z ðr; hÞ ¼ ðE o =cÞJ 1 ðk c rÞ sin h; where k c (¼ 1.841/a) is the cutoff wave number for the TE 11 mode. The electric field in the presence of plasma gets modified as 11,31 E P ðrÞ ¼ E rP ðr; hÞr þ E hP ðr; hÞĥ;…”
Section: A Temporal Variation Of the Electron Currentmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 The vacuum TE 11 mode is modified due to the plasma dispersion, hence the axial wave magnetic field amplitude can be expressed in terms of vacuum electric field amplitude E o for a cylindrical waveguide of radius a as 32 B z ðr; hÞ ¼ ðE o =cÞJ 1 ðk c rÞ sin h; where k c (¼ 1.841/a) is the cutoff wave number for the TE 11 mode. The electric field in the presence of plasma gets modified as 11,31 E P ðrÞ ¼ E rP ðr; hÞr þ E hP ðr; hÞĥ;…”
Section: A Temporal Variation Of the Electron Currentmentioning
confidence: 99%
“…10 It is shown that the waves can propagate through plasmas that are overdense in the steadystate approximation. [9][10][11] There are reports on the observation of charge oscillations in preformed steady state plasmas subjected to an external electric field [12][13][14] where the plasma is produced by a different source. The plasma oscillations are analyzed in collision-free and fully ionized regime in understanding the underlying phenomena.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…More recent research that is directly or indirectly associated with electrostatic plugging of magnetic cusps includes antihydrogen-related research [10,[31][32][33] and fusion-related research [34]. It should also be noted that recent research has been reported involving plasmas confined or controlled by multiple magnetic cusps [35,36]. The electrostatic-plugging research described in Refs.…”
Section: Inner Wellmentioning
confidence: 99%
“…The motivation further arises from the fact that, normally in most wave assisted plasma devices, the heating frequency is maintained constant (e.g., 13.56 MHz for rf discharges and 2.45 GHz in microwave discharges [11][12][13]), and two important parameters that may be varied are the system length (size) and the pressure, which can determine the dynamics of the particles (electrons and ions) present in the discharge. In many actual experiments, it may be inconvenient and quite cumbersome to vary the length of the system.…”
Section: Introductionmentioning
confidence: 99%